MORPHOLOGICAL VARIATION OF THE ECOTYPES OF Echinochloa crus-galli var crus-galli (L). Beauv (Barnyard grass: Poaceae) IN MALAYSIA and INDONESIA - SOET1KNO S SASTROUTOMO; ABDUL SHUKOR JURAIMI; JUGAH KADIR; SUHAIMI NAPIS; ARIFIN TASRIF (SEAMEO BIOTROP, 2004)
Greenhouse experiments were conducted to examine the morphological traits of barnyard grass ecotypes from diverse geographic origin. Seeds (caryopsis) were collected from 17 locations of rice fields throughout Malaysia (11 states) and Indonesia (six provinces) and were grown in pots each containing 10 kg of paddy field soil. The experiments were arranged using completely randomized design (CRD) with five replicates. Mean separation was calculated using Duncan multiple range test at 5% probability level. Unweighted pair-group method of arithmetic averages (UPGMA) was performed to determine the individual relationship within ecotypes of barnyard grass. Twelve morphological traits such as culm, panicle, leaf, and spikelet traits were measured. The growth characters such as emergence date, heading time, and growth duration were also evaluated. The average of emergence date, heading time, and growth duration of barnyard grass collected from Perils, Kedah, Penang, and Johor were relatively earlier than other ecotypes. Six groups were classified based on the cluster analysis of Malaysian ecotypes of barnyard grass. Principal component indicated that group six was found to be highly variable compared to others. While three groups were identified in Indonesian ecotypes of barnyard grass. Group one was observed to be highly variable. Results demonstrated that morphological variation among ecotypes of barnyard grass showing differences between the two regions illustrate the role of geographic variation. Key words : Variation / ecotypes / paddy field weeds / barnyard grass.